PREPARING FOR PREGNANCY PATIENTS WITH CHRONIC ENDOMETRITIS AND ITS EFFECTIVENESS - Наталья Ильинична Фадеева (Мать и дитя в Кузбассе, 2017)
The purpose of this research – comparative efficiency evaluation of pregravidarny preparation with use phyto - or physical therapy at patients with a chronic endometritis.